Study of a Fractional-Order Epidemic Model of Childhood Diseases. (16th July 2020) - Ullah, Aman; Abdeljawad, Thabet; Ahmad, Shabir; Shah, Kamal
Abstract : In this article, we discuss the existence and uniqueness of the solution of the fractional-order epidemic model of childhood diseases by using fixed point theory. The technique of natural transform coupled with the Adomian decomposition is used to find the solution of the proposed model. At the end of the article, the model is demonstrated with appropriate numerical and graphical description.